TINJAUAN HISTORIS PEMBAGIAN HADIS BESERTA MACAM- MACAM HADIS - Fina Sabrina Rahmawati; Muhamad Fatoni (DIRAYAH : Jurnal Ilmu Hadis, 2023)
As a Muslim we must realize that the hadith of the Prophet is the second source of law after the Al-Qur’an which is important for us to study and make it a guide to life. But before the period of bookeeping of hadiths took place, there were some irresponsible parties who made fake hadiths for their own sake, political or because of their stupidity, which caused the Hadith Ulama to create in depth and detailed methods to find out hadiths that really came from Prophet, so that the division of hadith is created which is seen from various aspects. Starting from shahih hadiths, ahad hadiths, dhaif hadiths, and several other hadiths. This research is library research with analytical-descriptive analysis. The aim of this research is to determine the division of hadith and various types of hadith based on historical review.